Assessment of eco-driving concepts within UMP community - Shanmugam, Subramaniam (2016)
Increased road transportation activities have resulted in increased burden on the environment. In particular, transportation generate pollution in the form of greenhouse gases associated with global warming. Eco-driving is the concept used to reduce fuel consumption, greenhouse gas emission and crash rates. This study was concerned on the assessment of eco-driving concepts within UMP community. The study aimed on to determine the understanding of eco-driving and how far UMP drivers adopt the ecodriving concepts. This study limits its study area to University Malaysia Pahang Campus Gambang. Based on the study, data for understanding of eco-driving, practicing of ecodriving and how often they practicing eco-driving in their journey were obtained from 240 participants at University Malaysia Pahang Campus Gambang. Results shows that a majority of UMP community understood about eco-driving concepts but there is a few number of participants still do not understand about eco-driving concepts where most of them are students. This is because the information about eco-driving is not fully conveyed to the students. Study concluded that 80% of UMP communities understood about the eco-driving and 162 of respondents out of 240 they do not ready to adopt the eco-driving concepts in their journey.